[Glaumbær Complex and Church From Road] - Streng, Evelyn Fiedler (1975)
Photograph of sod houses and a church at the Glaumbær Complex. The sod buildings form hill like structures covered in grass. Two white farmhouse faces sit on two of the hill at the center of the photograph. A hill dotted with animals and people sits to the left of the farmhouses surrounded by a wooden fence. A white church covered in a red roof is sat behind the houses. A mountain is visible in the background to the right.